The price of survival Marcus Levin, Norwegian Holocaust humanitarian - Berman, Irene Levin 1938- (Hamilton Books, 2019)
In this book, Irene Levin Berman tells the story of her father's heroic attempts to save the Jews of Norway, as well as hundreds of stateless refugees who escaped to Norway in the 1930s, from deportation to Nazi concentration camps during World War II. Marcus Levin worked tirelessly to help Jews before, during, and after the Nazi invasion of Norway. In 1962 he was awarded a Medal of Honor by King Olav of Norway for his efforts--back cover